Dasar Teologi tentang Misi Penginjilan - Sarah Wassar (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
God involves humans by giving missionary responsibility to His people to be involved in God's work of salvation. Every believer has a missionary task. Mission is centered and comes from God who is the core of His eternal plan for the salvation of humans from all His creations. Due to the lack of knowledge and methods about biblical mission teaching in the church and Christian institutions, the problems that arise in the form of mission and evangelism services are not a priority in the church, even congregations that have not responded or have not dared to carry out mission and evangelism services so that the church lacks missionaries. In this study, the method used is qualitative descriptive with an approach to an understanding and comprehension of the importance of biblical mission and evangelism and true and in-depth knowledge of the basics of mission and evangelism theology. Thus, every believer is called and responsible to carry out mission and evangelism in accordance with the great commission of the Lord Jesus Christ.